Digital Culture and Value Internalization in Islamic Banking: Understanding Customer Behavior in the Digital Era - Suad Fikriawan (Universitas Islam Negeri (UIN) Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: The rapid development of digital technology has transformed the way customers interact with banking services, including within the Islamic banking sector. While previous studies have predominantly focused on technological determinants of digital banking adoption, limited attention has been given to the integration of Islamic value internalization and digital culture in explaining customer behavior. This study aims to examine the relationship between digital culture and the internalization of Islamic values in shaping Islamic banking customer behavior in the digital era. Research Methods: This research employs a qualitative approach based on a literature review of relevant scientific articles. The analysis integrates the Unified Theory of Acceptance and Use of Technology (UTAUT2) framework with key Islamic value dimensions, including trust, Sharia compliance, transparency, and fairness. Through thematic analysis, the study develops an integrative conceptual framework that explains the interaction between technological and value-based factors in influencing customer behavior. Conclusion: The findings indicate that the adoption of digital banking services is influenced not only by technological factors such as perceived usefulness, ease of use, and service quality, but also by the internalization of Islamic values that shape customer trust, satisfaction, and loyalty. Digital culture serves as a contextual force that accelerates behavioral change and reinforce value based decision making. The study proposes the concept of digital value hybrid behavior, reflecting the integration of technological rationality and normative rationality.